ATP6AP2 ameliorates inflammation and pyroptosis in heart failure by promoting lysosome-dependent STING degradation - Xuan Zhao; Hui Zhang; Xinyue Ding; Huimin Wu; Min Li; Nengpin Yin; Junqing Gao; Youlong Xu; Rui Wang; Zhen Qi; Lina Xing; Zongjun Liu (Apoptosis, 2026)

Compartmental pH regulation in cancer and antitumor immunity: therapeutic opportunities and challenges - Fangquan Chen; Xiutao Cai; Qile Zhou; Zhen Huang; Jie Wang; Rui Kang; Daolin Tang; Jiao Liu (Apoptosis, 2026)

GPx6 downregulation drives ferroptosis in Kashin-Beck disease chondrocytes via the SLC7A11/GPx4 axis - Yinan Liu; Jie Li; Meng Zhang; Ying Zhang; Mengying Wang; Rui Wang; Xiaoming Zhao; Pinglin Yang; Jinghong Chen; Jian Sun (Apoptosis, 2026)

SIRT1-regulated mitophagy mitigates lipotoxicity-induced ferroptosis in diabetic kidney disease - Yingchun Jian; Yongqin Zeng; Zhengdi Wang; Xingyan Zhou; Haiping Zhang; Dan Liang; Rui Yan (Apoptosis, 2026)

Intermodulation of endoplasmic reticulum stress and ferroptosis in diabetic nephropathy: molecular mechanisms and therapeutic potentials - Jiyang Wang; Fengxia He; Runxiu Wang; Fangqin Zou; Wenjun Yan; Shengyu Cheng; Rui Liu; Xianghong Lei (Apoptosis, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

A new perspective on iron-dependent cell death: PRDX-1-mediated ferroptosis in tumor cells - Rui Li; Zhiyuan Wang; Yueyue Yujiang; Mengyuan Hu; Hongkun Zhao; Fei Yan (Apoptosis, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Necroptosis in obesity: a complex cell death event - Zunhai Liu; Simeng Wang; Wentao Wang; Rui Lv; Chao Sun (Apoptosis, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

The STING signaling pathways and bacterial infection - Jiayi You; Ailing Xu; Ye Wang; Guangmin Tu; Rui Huang; Shuyan Wu (Apoptosis, 2025)

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

LncRNA MIR210HG promotes phenotype switching of pulmonary arterial smooth muscle cells through autophagy-dependent ferroptosis pathway - Enze Wang; Binbin Zhang; Ling Huang; Pulin Li; Rui Han; Sijing Zhou; Daxiong Zeng; Ran Wang (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

Crosstalk of ferroptosis regulators and tumor immunity in pancreatic adenocarcinoma: novel perspective to mRNA vaccines and personalized immunotherapy - Yanlong Shi; Yizhu Wang; Hui Dong; Kaiyi Niu; Wenning Zhang; Kun Feng; Rui Yang; Yewei Zhang (Apoptosis, 2023)
Pancreatic adenocarcinoma (PAAD) is the eighth leading cause of cancer-related mortality that causes serious physical and mental burden to human. Reactive oxygen species accumulation and iron overload might enable ferroptosis-mediated cancer therapies. This study was to elusive novel ferroptosis regulator and its association with immune microenvironment and PD-L1 in PAAD. RNA-seq data and relevant information were obtained from The Cancer Genome Atlas and Genotype-Tissue Expression. The R packages “ggplot2” and “pheatmap” were used to the expression of 20 ferroptosis regulators between PAAD and normal tissues. The R package “ConsensusClusterPlus”, “survival”, “survminer”, “immunedeconv”, and TIDE algorithm performed consensus clustering, overall survival, progression-free survival, disease free survival, immune infiltration level, and immunotherapy responses between cluster 1 and cluster 2. The prognostic value was confirmed by the Kaplan–Meier curves, receiver operating characteristic curve, univariate and multivariate cox regression, and nomogram. Moreover, the relationship of FANCD2 and immunity, drug sensitivity was investigated by R package “ggstatsplot”, “immunedeconv”, “ggalluvial” and “pRRophetic”. Besides, the qRT-PCR, immunohistochemistry and western blotting detected the expression of FANCD2 in PAAD cell lines. Most ferroptosis regulators were up-regulated in PAAD, while the expression of LPCAT3, MT1G, and GLS2 was down-regulated in PAAD (P

The role of autophagy in pulmonary hypertension: a double-edge sword - Rui Chen; Meiping Jiang; Bo Li; Wei Zhong; Zhongqun Wang; Wei Yuan; Jinchuan Yan (Apoptosis, 2018)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

Airborne fine particulate matter induces multiple cell death pathways in human lung epithelial cells - Xiaobei Deng; Fang Zhang; Lijuan Wang; Wei Rui; Fang Long; Yong Zhao; Deliang Chen; Wenjun Ding (Apoptosis, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Preparation and bioevaluation of 99mTc-HYNIC-annexin B1 as a novel radioligand for apoptosis imaging - Quan-Yong Luo; Fang Wang; Zhi-Yong Zhang; Yi Zhang; Han-Kui Lu; Shu-Han Sun; Rui-Sen Zhu (Apoptosis, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Involvement of PDCD5 in the regulation of apoptosis in fibroblast-like synoviocytes of rheumatoid arthritis - Ning Wang; Hou-Shan Lu; Zhen-Peng Guan; Tie-Zheng Sun; Ying-Yu Chen; Guo-Rui Ruan; Zhan-Kun Chen; Jun Jiang; Chu-Jie Bai (Apoptosis, 2007)

Grifolin induces apoptosis via inhibition of PI3K/AKT signalling pathway in human osteosarcoma cells - Song Jin; Rui-Ping Pang; Jing-Nan Shen; Gang Huang; Jin Wang; Jia-Guo Zhou (Apoptosis, 2007)

Role of iNOS-derived reactive nitrogen species and resultant nitrative stress in leukocytes-induced cardiomyocyte apoptosis after myocardial ischemia/reperfusion - Xiao-Liang Wang; Hui-Rong Liu; Lin Tao; Feng Liang; Li Yan; Rong-Rui Zhao; Bernard L. Lopez; Theodore A. Christopher; Xin-Liang Ma (Apoptosis, 2007)